Marginal zone lymphoma-associated antiphospholipid antibodies successfully treated with bendamustine rituximab. Issue 3 (14th March 2019) - Liu, Ziyang; Markham, Merry; Mandernach, Molly W
Abstract : A 46-year-old man presented with splenomegaly, abdominal adenopathy and profoundly elevated prothrombin time and partial thromboplastin time. He was diagnosed with marginal zone lymphoma (MZL) and small lymphocytic lymphoma, and the abnormal coagulation studies were secondary to the presence of a lupus anticoagulant. Optimal upfront therapy for MZL has not been established, and the incidence of antiphospholipid antibodies (APLA) in this patient population is rare. Following treatment with six cycles of bendamustine and rituximab with 2 years of rituximab maintenance, our patient remained in remission and his coagulation studies normalised. This report describes a case of successful treatment of APLA associated with MZL that resolved after treatment of the lymphoma.